The Role Of Work Comfort In Mediating The Influence Of Job Stress And Work Encouragement On The Performance Of Pt Brr Desa Sanur Employees - Paulus Tahu, Gregorius; Winarsih, Winarsih; Landra, Nengah (Jurnal Ekonomi, 2024)
The purpose of this study was to analyze the influence of role, job satisfaction and motivation on working employees at PT. BPR Sanur Village. This study involved 46 employees as respondents, and public information was collected through questionnaires that were analyzed using analytical methods. The results of the study indicate that work stress has a negative effect on employee job satisfaction, while working directly has a positive effect on job satisfaction. Job satisfaction has been proven to be a mediator that connects work stress and work motivation with employee performance. This research report is also equipped with data validity and reliability tests which show that all variables and indicators used are valid and reliable. In addition, normality and multicollinearity tests were also reported with satisfactory results. Regression analysis shows that job satisfaction can explain 61.7% of employee performance variations. This study concludes that controlling work stress and increasing motivation are important in employee development. Therefore, companies need to use strategies to manage stress and create motivation to be better at achieving organizational goals.